Correlation between Depression and Anxiety and the Level of Vitamin B12 in Patients with Depression and Anxiety and Healthy Controls - Aleksandar Todorov; Petranka Chumpalova-Tumbeva; Maya Stoimenova-Popova; Vanya Popova; Doroteya Todorieva-Todorova; Nikolai Tzvetkov (Journal of Biomedical & Clinical Research)
Affective disorders, including depression, are of great social importance and lead to serious everyday life infringement and disability. Affective disorders are one of the main causes of suicide causes. Anxiety disorders represent a variety of psychic disorders that often lead to disability. Anxiety and depression syndromes together are often seen in patients. Vitamin B12 (cobalamin) is the only vitamin containing cobalt. Our aim was to investigate, evaluate and compare depression and increased anxiety and serum Vitamin B12 level in patients with depression, in patients with Vitamin B12 deficiency anemia and healthy controls. We investigated 74 subjects – 38 patients and 36 healthy controls. Serum Vitamin B12 level was measured in all participants. It is assumed that normal ranges of Vitamin B12 level vary. The most recently accepted ones are 200 to 900 pg/ml. In cases of levels below 200 pg/ml, a therapy with vitamin B12 should be applied. On the other hand, the level necessary for normal biochemical processes is higher – 250 pg/ml. In our study, serum Vitamin B12 level in more than 50% of patients with depression/anxiety was below 200 pg/ml, and in more than 60% of these patients it was below 250 pg/ml.